Body image and well-being in dance practitioners: An exploratory study - Faria, B. (2021)
Literature has been concerned with the effect of dance practice on several variables, namely well-being and body image (BI). This study aimed to analyse the perception of dance practitioners on BI and subjective well-being (positive and negative affect and satisfaction with life), comparing adolescents and adults. A sample of 91 dancers (18.08±5.12 years) was recruited and divided into two groups (adolescents 11-17 years; adults 18-34 years). The group of adolescents presented a higher perception of satisfaction with life compared to adults (p=0.041; d=-0.44). Regarding the relationships between variables, when analysing separately each group, in the group of adolescents the positive affect is related to satisfaction with life (r=0.64; p≤0.001) and negative affect (r=-0.32; p=0.026), while the negative affect is related to the hours of weekly practice (r=0.46; p=0.001). In the group of adults, positive affect is related to satisfaction with life (r=0.36; p=0.017) and weekly hours of practice (r=0.39; p=0.010), while negative affect is related satisfaction with life (r=-0.45; p=0.003). With regard to (dis)satisfaction with BI, we found that, in the group of adolescents, it is related to the years of practice (r=0.33; p=0.023) and the weekly hours of practice (r=0.32; p=0.023), while in the adults' group, satisfaction with life (r=-0.42; p=0.005) and negative affect (r=0.59; p≤0.001) are related. Our results leave some indicators that should be explored in future studies, namely seeking to understand the factors that may be mediating the relationship between BI and well-being, as well as the effect of age on this relationship.